The Transformative Impact of Artificial Intelligence in Healthcare: Innovations, applications, and future prospects - Shen Ruoyu (SHS Web of Conferences)
The modern applications of artificial intelligence (AI) are influencing developments in healthcare that could lead to radical advancements through increased accuracy of diagnostics, customization of treatment planning, as well as better efficiency in healthcare operations. This study discusses the transformative applications of AI in healthcare, including how technologies such as machine learning, neural networks, deep learning, and natural language processing can be used for diagnosis, personalized medicine, predictive analytics, virtual health assistants, surgery, and rehabilitation. At the same time, the application of AI in healthcare poses a number of challenges, such as data privacy, algorithmic bias, and ethics. This study also explores the role of AI in global health, the need for policies and regulations, and the long-term impact of AI on future healthcare systems. Despite multiple challenges, the continued innovation and development of AI in healthcare bodes well for a more efficient, accurate, and accessible healthcare delivery system in the future.